Assignment of the human homologue of the mouse t-complex gene TCTE3 to human chromosome 6q27 - Rappold, Gudrun; Trowsdale, John; Lichter, Peter (Genomics, 1992)
The gene TCTE3 from the mouse t-complex region is expressed specifically in testicular germ cells. It maps in the central subregion of the t-complex on mouse chromosome 17 containing loci involved in transmission ratio distortion and male sterility. In this study, somatic cell hybrid lines have been used to map the human homologue, TCTE3, to the long arm of chromosome 6. CISS hybridization with the human λ clone h117 refined this chromosome assignment to the very distal position of chromosome 6q27, thus providing further evidence that loci from the t-complex of mouse chromosome 17 can map to opposite arms of human chromosome 6.
Online 29 October 2004
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 31.03.2021